Association of lifestyle-related factors and psychological factors on quality of life in people with schizophrenia - Costa, Raquel (2018)
In people with schizophrenia several factors are associated with poor quality of life (QoL), namely, lifestyle-related factors and psychological factors. However, there has been little research on the impact of these factors on QoL. Therefore, the relation between lifestyle-related factors, psychological factors, and QoL in people with schizophrenia was assessed. A cross-sectional study was conducted among 115 patients (25% women, 50% inpatients). QoL was measured by World Health Organisation Quality of Life- Brief Version. Lifestyle-related factors were assessed, namely physical activity (International Physical Activity Questionnaire- Short Form), sleep quality (Pittsburgh Sleep Quality Index) and dietary intake (Mediterranean Diet score). Psychological factors such as self-esteem (Rosenberg Self-Esteem Scale) and autonomous motivation (Behavioural Regulation Questionnaire- version 3) were also measured. Regression analyses were performed to identify significant predictors of QoL. Results showed that self-esteem predicted better global, physical, psychological and environmental QoL. Physical activity predicted better global and physical QoL, while sedentary time predicted poor social and environmental QoL. Identifying predictors of QoL has implication for the effective design and delivery of lifestyles interventions, including physical activity, dietary education and smoking cessation in people with schizophrenia. Adopting healthy lifestyles may lead to improved physical health, psychological well-being and QoL in this population.